2020
DOI: 10.1371/journal.pone.0235759
|View full text |Cite
|
Sign up to set email alerts
|

Proximal renal tubular function in HIV-infected children on tenofovir disoproxil fumarate for treatment of HIV infection at two tertiary hospitals in Harare, Zimbabwe

Abstract: BackgroundRenal abnormalities in HIV infected children may be due to the HIV infection or treatment among other factors. Tenofovir disoproxil fumarate (TDF) is associated with proximal renal tubular dysfunction, proteinuria and decrease in glomerular function. Studies in developed countries have shown variable prevalence of proximal renal tubular dysfunction in children on TDF. There are no known studies in developing countries, including Zimbabwe, documenting the proximal tubular function in HIV infected chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The most common biomarker used for CKD diagnosis was serum creatinine measured by the enzymatic method. Estimated GFR (eGFR) was used in 13 studies alone and in combination with markers of kidney damage (6, 33, 4447, 5153, 5558). Five studies used an eGFR cut-off of <60ml/min/1.73m 2 (4446, 55, 57), two used this cutoff alone without any marker of kidney damage (45, 57) and six used a cut-off of <90ml/min/1.73m 2 (6, 33, 47, 51, 53, 58).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common biomarker used for CKD diagnosis was serum creatinine measured by the enzymatic method. Estimated GFR (eGFR) was used in 13 studies alone and in combination with markers of kidney damage (6, 33, 4447, 5153, 5558). Five studies used an eGFR cut-off of <60ml/min/1.73m 2 (4446, 55, 57), two used this cutoff alone without any marker of kidney damage (45, 57) and six used a cut-off of <90ml/min/1.73m 2 (6, 33, 47, 51, 53, 58).…”
Section: Resultsmentioning
confidence: 99%
“…However, only four studies fulfilled the chronicity criteria; three studies repeated the tests after more than 3 months (47, 51, 55), and one study repeated the tests after only one month (49). Three studies used a cut-off of <90 ml/min/1.73m 2 which does not fit the KDIGO definition and tended to overestimate the CKD prevalence (6, 53, 54). Other studies used ranges such as 60-90 or 30-60 ml/min/1.73m 2 potentially underestimating the CKD prevalence (45, 51).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of Zimbabwean children and adolescents < 18 years and on TDF found hypophosphataemia, proteinuria and a decreased eGFR of < 90 mL/min per 1.73 m² in 11.1%, 32.8% and 35.9%, respectively. 47 Proteinuria and a lower eGFR were associated with concomitant protease inhibitor (PI) use. 47 It is difficult to compare studies, as participants in the Zimbabwean study were younger with a shorter duration of ART, and VL was not evaluated because of cost restraints.…”
Section: Discussionmentioning
confidence: 99%
“… 47 Proteinuria and a lower eGFR were associated with concomitant protease inhibitor (PI) use. 47 It is difficult to compare studies, as participants in the Zimbabwean study were younger with a shorter duration of ART, and VL was not evaluated because of cost restraints. We found no evidence of hypophosphataemia, phosphaturia, proteinuria or renal impairment 24 weeks after the switch to TDF-containing ART.…”
Section: Discussionmentioning
confidence: 99%
“…16 Reduction in estimated glomerular filtration rate (eGFR) < 90 ml/min/1.73 m 2 and proteinuria was evident in 35.9% and 32.8% of children, respectively for those on ART. 17…”
Section: Introductionmentioning
confidence: 99%